ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENERAPAN KONSERVATISME AKUNTANSI - Muhammad Ridho; Dwi Arianto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2022)
This study aims to examine the factors that influence accounting conservatism in food sector manufacturing companies on the Indonesia Stock Exchange (2018-2020). The factors tested are leverage ratio, firm size, capital intensity, and managerial ownership. This study uses 15 food sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period as research samples. Hypothesis testing uses the 2018-2020 regression analysis model to test the leverage ratio, firm size, capital intensity, and managerial ownership on accounting conservatism. The results show that firm size, capital intensity and managerial ownership have a positive effect on accounting conservatism, while the leverage ratio has a negative effect. against accounting conservatism. Keywords: leverage ratio, firm size, capital intensity, managerial ownership.